Use of biosaline water in the germination of seeds of Caatinga forest species - a review (Research, Society and Development, 2021)
With the reduction of good quality water and the increase of biosaline water in the world, studies on the production of seedlings of forest species are necessary, since there is a need for recovery of degraded areas and these may be subject to various stresses, especially saline. The present literature review aims to evaluate scientific articles about the use of biosaline water in the germination of seeds of Caatinga forest species, as well as to investigate the themes addressed (salinity, salt stress, biosaline water, salts on seed germination, salinity tolerance, strategies for use of biosaline waters, seedling production with biosaline waters, forest seeds subjected to salinity) in the publications, languages adopted (Portuguese, English and Spanish) and the number of articles per database. With the themes used, it was possible to find a very high number of articles in the databases (Scielo, Web of Science, Periódico Capes and Google Scholar) during the 20 years analyzed, totaling 217,477. However, with more in-depth study of the themes for Caatinga forest species, this number was drastically reduced, reaching 183 articles, with a greater predominance in the Google Scholar database. The results suggest that more research is needed regarding the saline stress to which Caatinga forest species are subjected, since salinity is a reality in this dry tropical forest.